Mechanism of damnacanthal induced apoptosis in CEM-SS cell line - Gopalsamy, Banulata; Saiful Yazan, Latifah; Abdul Hamid, Hisyam (Penerbit Universiti Kebangsaan Malaysia, 2024)
Leukaemia, is cancer of organs that is responsible to produce blood specifically the lymphatic system and bone marrow. Due to the harsh effects of currently used cancer drugs, damnacanthal, an anthraquinone obtained from the roots of Morinda elliptica is tested as a potential anticancer agent. This study reports on the participation of the p53, Bcl-2 and Bax in the apoptosis induced by of damnacanthal, on T-lymphoblastic leukaemia (CEM-SS) cell. Cell viability and morphology was tested with trypan blue assay, flow cytometry analysis detected the apoptotic activity of damnacanthal, caspase colorimetric protease assay tested the Caspase 2, 3, 6, 8, and 9’s involvement and Enzyme-linked Immunosorbent Assay (ELISA) was carried out to quantify the Human p53, Bcl-2, and Bax expression levels. Damnacanthal exhibited cytotoxicity at doses 10 and 30 µg/mL after 72 h of incubation. This study reports that damnacanthal arrested the cell at G2/M phase and initiates the apoptotic activity in the cells treated with 30 µg/ mL of damnacanthal for 72 h through caspase 2 and 6 activation and not caspases 3, 8, and 9. Furthermore, this anthraquinone induces apoptosis via p53-independent pathway. Damnacanthal also lowered Bcl-2 and increased Bax activity in CEM-SS cell lines. These anticancer properties of damnacanthal makes it a potential agent to treat T-lymphoblastic leukaemia. © 2024 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.